Analysis of green coffee quality using hermetic bag storage. (January 2019) - Donovan, Natalie K.; Foster, Kenneth A.; Parra Salinas, Carlos Alberto
Abstract: Coffee ( Coffea arabica L .) value is highly dependent on quality. However, due to high humidity in the Central Andean Ranges of Colombia, where much of the country's coffee production resides, Farmers must sell their coffee at harvest in order to mitigate quality loss due to the high moisture. Cooperatives are generally forced to store green coffee until enough volume is collected for export, making it crucial to utilize storage solutions that maintain quality over time. This study examines the efficacy of Purdue Improved Crop Storage (PICS) hermetic bags for storage of green coffee in a simulated small farm setting. PICS bags with the standard three layers (PICS3), PICS bags with two layers (PICS2), and Traditional jute sacks were studied. Quality indicators examined were moisture content, water activity, and cupping score. Analysis of coffee stored at monthly intervals over seven months suggests that both versions of PICS show promise in maintaining moisture content, water activity, and sensory scores. Furthermore, the data suggest that water activity is a better indicator of quality than the currently used moisture content and there is no statistically significant difference in performance between the two PICS treatments. Highlights: Hermetic bags maintained green coffee quality during storage in a humid environment of the Central Colombian Andes. No statistical difference was found between PICS bags with two or three layers during prolonged storage. Water activity appears to be a superior indicator of green coffee quality than the commonly used moisture content.